Development of contextual interactive e-modules on the human organ system to support SDGs - Idah Hamidah; Lesy Luzyawati; Anilia Ratnasari (Universitas Muhammadiyah Malang, 2025)
Technology-based learning is one of the outcomes of the 4.0 industrial revolution that supports the implementation of Sustainable Development Goals (SDGs) in education The use of teaching materials in the form of contextual-based interactive e-modules is still rarely used in schools. The use of teaching materials that are common in schools are teaching materials that have been provided by the government and book publishers so that they are less in accordance with student needs. This study aims to produce contextual-based interactive e-modules on the material of the human organ system. This research is included in Research and Development (R&D), by following the Four-D development model consisting of the define, design, development, and disseminate stages. However, this study was limited to the development stage. The subjects of this study were two grade XI biology teachers at SMAN in Indramayu Regency, West Java, seven doctors, and four validators. The results of the study showed that the developed e-module obtained validation results in the context of material, language, and digital teaching materials that were very good with an average score of 96.82%. Further research can be continued at the disseminate stage to see the effectiveness of the e-module.